Resilience of primary healthcare facilities: Experiences from 16 European countries during the COVID-19 pandemic. A mixed-methods study conducted by EURIPA - Petrazzuoli, Ferdinando; Gokdemir, Ozden; Antonopoulou, Maria; Blahová, Beata; Mrduljaš - Đujić, Natasa; Dumitra, Gindrovel Gheorghe; Falanga, Rosario; Ferreira, Mercedes; Gintere, Sandra; Hatipoglu, Sehnaz; Jacquet, Jean-Pierre; Javorská, Kateřina; et al. (Advances in clinical and experimental medicine : official organ Wroclaw Medical University, 2025)
The role of primary healthcare (PHC) during a pandemic varies across European countries. The coronavirus disease 2019 (COVID-19) pandemic has altered the working practices of family medicine doctors and impacted the resilience of healthcare systems. This study aimed to examine European healthcare system responses to the pandemic, focusing on rural and urban differences. This cross-sectional, mixed-methods study used a semi-structured online questionnaire with 68 questions, including 21 free-text comments. Data were collected from May 2020 to January 2021. Key informants from 16 European Rural and Isolated Practitioners Association (EURIPA) member countries distributed questionnaires to 406 PHC doctors. Data were analyzed using descriptive statistics and nonparametric tests (χ2, Kruskal-Wallis, Mann-Whitney U) with a significance threshold of 0.05. A statistically significant difference was found between rural (36.4%, 55/151), semirural (19.4%, 24/124) and urban populations (29.8%, 39/131) regarding medicine shortages (χ2 = 9.91, degrees of freedom (df) = 4, p = 0.042). The semirural setting showed a statistically significant difference from the other settings (p = 0.004 in post hoc χ2 test). Significant differences were found between countries in resilience features including, effectiveness of triage, adapting to the rapidly changing requirements, government help, existence of a community resilience group, improved interprofessional collaboration, medicine shortage, and general practitioners (GPs) involvement in palliative care. Medicine shortage was more prevalent in rural and urban areas compared to semirural areas. Differences were observed between countries in their responses to the pandemic, particularly in adapting to the rapidly changing requirements, effectiveness of triage, government help, and the existence of a community resilience group. These differences were confirmed with qualitative analysis. The results emphasize the need for tailored approaches considering diverse contexts in shaping effective healthcare system resilience.